Percussion assisted radiation therapy in Hodgkin lymphoma allows a marked reduction in heart dose. (November 2020) - Durham, André-Dante; Lovis, Alban; Simons, Julien; Long, Olivier; Buela, Flore; Ogna, Adam; Jumeau, Raphaël; Cairoli, Anne; Rocha Do Carmo Leal, Susana; Zeverino, Michele; Patin, David; Vallet, Véronique; et al.
Highlights: We previously showed that high frequency percussion could induce "apnea-like" lung stabilisation of 20 min or more. This percussion assisted radiotherapy was routinely used in a series of patients with Hodgkin lymphoma. All treatment sessions were performed safely without interruption. A significant and clinically meaningful reduction of the dose to the heart was observed. This is the first evidence of a potential benefit associated with this technique. Abstract: Background and purpose: Early-stage Hodgkin lymphoma (HL) is a highly curable disease but the treatment can induce late complications many years later. Irradiation of the healthy heart is inevitable during radiation treatment of mediastinal sites. We developed a novel method to induce a prolonged apnea-like state that can help decrease the dose to organs at risk during radiation therapy. We present the results of the first 8 HL patients treated routinely with percussion assisted radiation therapy (PART) in our clinic. Material and methods: We used a newly developed high-frequency non-invasive ventilation system to suppress respiratory motion for prolonged periods and push the heart away from the treated volume. Results: All 8 patients were able to rapidly learn the technique and had an advantage to be treated by PART. We lowered the mean heart dose by an average of 3 Gy with similar target coverage compared to a classical free breathing treatment plan. They were all treated for 15 radiotherapy sessions by PART without any notable side effects. Conclusions: Percussion assisted radiation therapy can be used routinely to reduce the dose to the heart in Hodgkin lymphoma.